Reinforcing production cooperation and dialogue spaces : the role of SMEs - Rovira, Sebastián (UN ECLAC SantiagoCL, 2015)
Discusses the main obstacles facing SMEs - limitations in terms of human capital, financing, innovation capacities, institutional and business setting, production linkages and access to global value chains. Takes a comparative approach vis-a-vis the experience of the European Union countries to identify areas in which the two regions could intensify cooperation efforts.